Characterizing non-fluent aphasia in English-based Caribbean creole languages: A case study - McDonald, Ruth (My University, 2014)
Impairment caused by non-fluent aphasia often results in the omission and substitution of inflectional markers. Cross-linguistic work has revealed differential patterns of aphasic impairment across languages. This study aims to determine how non-fluent aphasia is manifested in English-based Caribbean creole languages, namely Jamaican Creole English (JCE) and Guyanese Creole (GC). The use of inflectional morphology is variable in English-based Caribbean creole languages. Therefore, in aphasic creole speech, it is difficult to ascertain the status of a grammatical omission as a valid creole feature or as a sign of impairment. I argue that Seymour’s et al. (1998) contrastive-noncontrastive schema can be useful for differentiating between normal and disordered creole features. The data in this study was obtained from a creole speaker with aphasic impairments. The data was later transcribed and analyzed. The results of this study appear to suggest that grammatical markers may form a hierarchy of susceptibility to aphasic impairment. Tense, agreement and aspectual markers along with auxiliaries and copulas appear to be more susceptible to impairment in disordered creole speech than plural markers, personal and demonstrative pronouns and articles.
Keywords: creole; inflectional morphology; non-fluent aphasia; speech therapy